Organization Patterns of Complex River Networks in Chile: A Fractal Morphology - Francisco Martinez; Hermann Manriquez; Alberto Ojeda; Gabriel Olea (Mathematics, 2022)
River networks are spatially complex systems difficult to describe by using simple morphological indices. To this concern, fractal theory arises as an interesting tool for quantifying such complexity. In this case of study, we have estimated for the first time the fractal dimension of Chilean networks distributed across the country, analysed at two different scales. These networks insert into variable environments, not only from a climatic and hydrological point of view, but also from a morphological point of view. We investigate to which extent the fractal dimension is able to describe the apparent disorganized character of landscape, by applying two methods. Striking patterns of organization related to Horton ratios and the fractal dimension are reported and discussed. This last parameter depends on the scale of the network, showing interesting groupings by tectonic and climatological factors. Our results suggest that under restricted conditions, the fractal dimension could help to capture the intricate morphology of Chilean networks and its links with the hydrological, climatic, and tectonic conditions present across the country.